The Passage of Years: Not a Matter of Covert Retrieval of Autobiographical Memories - Kosak, Ferdinand; Hilbert, Sven (Frontiers in Psychology, 2021)
In current research, variations in retrospective passage of time judgments for long intervals are commonly attributed to differences regarding the number of experiences in these intervals or the accessibility of the respective memories. This seems to imply the assumption of a covert retrieval, where authors presume that memories from the respective interval influence the experience of time without these memories being explicitly activated when judging. However, no studies have systematically investigated the relation between the experience of time and the respective experiences and memories. To this end, we analyzed data from three studies in which participants judged the passage of the last 5 years either before being asked to select outstanding life events from a list (Studies 1a and b; N = 293 and 263) or before recalling as many meaningful personal memories as were spontaneously accessible (Study 2; N = 262). Despite applying a statistically powerful trial-by-trial mixed-effects modeling approach, neither in the separate datasets nor in the combined dataset, passage of time judgments were predicted by the number of reported events or memories. This suggests that people's spontaneous judgments of the passage of multiannual intervals are not necessarily affected by a covert retrieval of memories from the respective period.